Photodynamic therapy combined to cisplatin potentiates cell death responses of cervical cancer cells - de Freitas, Laura Marise [UNESP]; Serafim, Rodolfo Bortolozo; de Sousa, Juliana Ferreira; Moreira, Thaís Fernanda [UNESP]; dos Santos, Cláudia Tavares [UNESP]; Baviera, Amanda Martins [UNESP]; Valente, Valeria [UNESP]; Soares, Christiane Pienna [UNESP]; Fontana, Carla Raquel [UNESP] (Springer Nature, 2017)
Background: Photodynamic therapy (PDT) has proven to be a promising alternative to current cancer treatments, especially if combined with conventional approaches. The technique is based on the administration of a non-toxic photosensitizing agent to the patient with subsequent localized exposure to a light source of a specific wavelength, resulting in a cytotoxic response to oxidative damage. The present study intended to evaluate in vitro the type of induced death and the genotoxic and mutagenic effects of PDT alone and associated with cisplatin. Methods: We used the cell lines SiHa (ATCC® HTB35™), C-33 A (ATCC® HTB31™) and HaCaT cells, all available at Dr. Christiane Soares' Lab. Photosensitizers were Photogem (PGPDT) and methylene blue (MBPDT), alone or combined with cisplatin. Cell death was accessed through Hoechst and Propidium iodide staining and caspase-3 activity. Genotoxicity and mutagenicity were accessed via flow cytometry with anti-gama-H2AX and micronuclei assay, respectively. Data were analyzed by one-way ANOVA with Tukey's posthoc test. Results: Both MBPDT and PGPDT induced caspase-independent death, but MBPDT induced the morphology of typical necrosis, while PGPDT induced morphological alterations most similar to apoptosis. Cisplatin predominantly induced apoptosis, and the combined therapy induced variable rates of apoptosis- or necrosis-like phenotypes according to the cell line, but the percentage of dead cells was always higher than with monotherapies. MBPDT, either as monotherapy or in combination with cisplatin, was the unique therapy to induce significant damage to DNA (double strand breaks) in the three cell lines evaluated. However, there was no mutagenic potential observed for the damage induced by MBPDT, since the few cells that survived the treatment have lost their clonogenic capacity. Conclusions: Our results elicit the potential of combined therapy in diminishing the toxicity of antineoplastic drugs. Ultimately, photodynamic therapy mediated by either methylene blue or Photogem as monotherapy or in combination with cisplatin has low mutagenic potential, which supports its safe use in clinical practice for the treatment of cervical cancer.
Keywords: Caspase-independent cell death; Cisplatin; Combined therapy; Methylene blue; Photodynamic therapy; Photogem